Mechanisms of HBV immune evasion - Kuipery, Adrian; Gehring, Adam J.; Isogawa, Masanori (Antiviral research, 2020)
The concept of immune evasion is a longstanding topic of debate during chronic Hepatitis B Virus infection. The 292 million individuals chronically infected by HBV are clear evidence that the virus avoids elimination by the immune system. The exact mechanisms of immune evasion remain undefined and are distinct, but likely interconnected, between innate and adaptive immunity. There is a significant body of evidence that supports peripheral tolerance and exhaustion of adaptive immunity but our understanding of the role that central tolerance plays is still developing. Innate immunity instructs the adaptive immune response and subversion of its functionality will impact both T and B cell responses. However, literature around the interaction of HBV with innate immunity is inconsistent, with reports suggesting that HBV avoids innate recognition, suppresses innate recognition, or activates innate immunity. This complexity has led to confusion and controversy. This review will discuss the mechanisms of central and peripheral tolerance/exhaustion of adaptive immunity in the context of chronic HBV infection. We also cover the interaction of HBV with cells of the innate immune system and propose concepts for the heterogeneity of responses in chronically infected patients. •HBV drives the exhaustion of both HBV specific T and B cells through peripheral tolerance.•T and B cell exhaustion differ: B cells are not deleted whereas HBV-specific T cells are found at extremely low frequencies.•Data regarding the interaction of HBV with innate immunity, particularly myeloid cells, remains highly contradictory.•Transient, immature, nature of myeloid cells in blood, and patient heterogeneity, will affect phenotype and function.